Indirect Correlation between Hotel’s Environmental Policy and its Performance through Employee's Environmental Abilities - I Ketut Gede, Sukaadha; Sulistyaningsih, Endang (Journal of Entrepreneurship and Business, 2024)
Pupose: This study examines the impact of employees' green abilities as a mediator on the relationship between hotel green policy and hotel green performance within a hotel group in Bali. Numerous efforts have been made to pursue business sustainability, particularly within the hospitality tourism sector. Method: The sample of this study consists of 161 employees with supervisor status working in the operations department, selected through convenience sampling. Data analysis was conducted using path analysis with Smart PLS. Result: The results reveal a significant direct effect of the Hotel Green Policy on Hotel Green Performance and a significant indirect effect through the mediator of employee's green abilities. Therefore, this study concludes that employees' green abilities mediate the significant indirect relationship between Hotel Green Policy and Hotel Green Performance.